Personal Color and Its Role in Enhancing Professional Branding and Self-Presentation in Makassar City, Indonesia - Andi Tahira Ashar (Public Resource Innovation Management and Excellence, 2025)
This study aims to explore the role of personal color in enhancing professional branding and self-presentation in Makassar City, Indonesia. Personal color is a color psychology-based approach that helps individuals choose colors that match their skin, hair, and personality characteristics, thus supporting a more attractive and authentic appearance. This study used a qualitative method with in-depth interviews with 15 young professionals from various sectors, such as banking, education, and entrepreneurship. The results showed that awareness of personal color contributed significantly to building a positive professional image, increasing self-confidence, and influencing others' perceptions of an individual's competence and credibility. In addition, knowledge of personal color helped participants choose appropriate clothing and accessories for various professional situations, including job interviews, presentations, and business events. This study recommends training and education on personal color to support self-development and professional branding, especially among young workers in Makassar. These findings provide insights for companies and individuals to utilize personal color as a strategy to increase competitiveness and professional success.